Irony as echoic mention: forms of echoes in concrete poetry - Koblizkova Wittlichova, Julie (Bohemica Olomucensia, 2020)
This paper deals with irony as a basic formal principal of concrete poetry. Based on Sperber and Wilson's theory of irony as echoic mention, it approaches concrete poem as a poetic form composed by two elements, which ironically mention one another. The ultimate target of this irony may be language or literature in general.
Keywords: Irony; concrete poetry; experimental poetry; echoic mention; Dan Sperber; Deidre Wilson